Children As Victims of Sexual Violence: Criminological Perspective - Waliulu, Muhammad Afgan; Sopacua, Margie Gladies (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Children are a mandate and a gift from God Almighty that must be safeguarded because they have human dignity and rights that must be upheld. Sexual violence crimes obtained by the Ambon City Police (POLRESTA) and Lease Islands during 2022 to 2024, the forms of sexual violence were in the form of sexual intercourse and sexual abuse of children.Purposes of the Research: This research aims to examine and discuss what are the factors that cause children to become victims of sexual violence at the Ambon City and Lease Islands Police Station.Methods of the Research: The research used in this legal writing is empirical legal research or non-doctrinal research (socio legal research), using the research approach used by the author is a qualitative approach where this approach is a research method that produces analytical descriptive data This research uses primary data and secondary data.Findings of the Research: The results showed that Factors causing children to become victims of sexual violence at the Ambon City and Lease Islands Police Department are 1) Lack of Education; 2) Psychological Disorders of the Perpetrator; 3) Technological Advancement Factor; and 4) Lack of Supervision from Parents.